The Role Of High Resolution Ultrasonography To Differentiate Between Benign And Malignant Cervical Lymph Nodes In Oral Squamous Cell Carcinoma (Update Dental College Journal, 2018)
Objectives:The purpose of the study was to evaluate the role of high resolution ultrasonography to differentiate between benign and malignant cervical lymph nodes in oral squamous cell carcinoma.Materials & Methods:The study was conducted in the Department of Oral and Maxillofacial Surgery, BSMMU,Dhaka, Bangladesh, during a period of January -2010 to December - 2011. A total number of 41 patients with clinical evidence of palpable cervical lymph nodes in oral squamous cell carcinoma were evaluated with high resolution ultrasonography. To evaluate the diagnostic accuracy of high resolutionultrasonography, the high resolution ultrasonography findings were compared and correlat- ed with histopathological examination after neck dissection.Results: All patients were pre-operatively examined by palpation and high resolution ultrasonography evaluation was done.Among them 41 study subjects, on high resolution ultrasonography evaluation 23(56.09%) lymph nodes were metastatic and 18(43.90%) lymph nodes were reactive. After postop- erative excisional histopathology examination 22(53.66%) lymph nodes were metastatic and 19(46.34%) lymph nodes were reactive in nature. Correlation of vascular flow pattern with histopatho- logical diagnosis showed that central flow for benign nodes, mixed & peripheral flow for malignant nodes were highly significant parameters (P